Prioritizing zoonotic diseases using a multisectoral, One Health approach for The Economic Community of West African States (ECOWAS) - Grace W. Goryoka; Virgil Kuassi Lokossou; Kate Varela; Nadia Oussayef; Bernard Kofi; Vivian Iwar; Casey Barton Behravesh (BMC, 2021)
Abstract Background Zoonotic diseases pose a significant threat to human, animal, and environmental health. The Economic Community of West African States (ECOWAS) has endured a significant burden of zoonotic disease impacts. To address zoonotic disease threats in ECOWAS, a One Health Zoonotic Disease Prioritization (OHZDP) was conducted over five days in December 2018 to prioritize zoonotic diseases of greatest regional concern and develop next steps for addressing these priority zoonoses through a regional, multisectoral, One Health approach. Methods The OHZDP Process uses a mixed methods prioritization process developed by the United States Centers for Disease Control and Prevention. During the OHZDP workshop, representatives from human, animal, and environmental health ministries from all 15 ECOWAS Member States used a transparent and equal process to prioritize endemic and emerging zoonotic diseases of greatest regional concern that should be jointly addressed by One Health ministries and other partners. After the priority zoonotic diseases were identified, participants discussed recommendations and further regional actions to address the priority zoonoses and advance One Health in the region. Results ECOWAS Member States agreed upon a list of seven priority zoonotic diseases for the region - Anthrax, Rabies, Ebola and other viral hemorrhagic fevers (for example, Marburg fever, Lassa fever, Rift Valley fever, Crimean-Congo Hemorrhagic fever), zoonotic influenzas, zoonotic tuberculosis, Trypanosomiasis, and Yellow fever. Participants developed recommendations and further regional actions that could be taken, using a One Health approach to address the priority zoonotic diseases in thematic areas including One Health collaboration and coordination, surveillance and laboratory, response and preparedness, prevention and control, workforce development, and research. Conclusions ECOWAS was the first region to use the OHZDP Process to prioritize zoonotic disease of greatest concern. With identified priority zoonotic diseases for the region, ECOWAS Member States can collaborate more effectively to address zoonotic diseases threats across the region using a One Health approach. Strengthening national and regional level multisectoral, One Health Coordination Mechanisms will allow ECOWAS Member States to advance One Health and have the biggest impact on improving health outcomes for both people and animals living in a shared environment.